COMPREHENSIVE REVIEW: RISK FACTORS ASSOCIATED WITH SOCIAL MEDIA ADDICTION AMONG YOUNG POPULATION - Srivastava, Upasna; Maheshwari, Aruna; Barmola, KC (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Young people’s addiction to social media is an increasing global phenomenon, fuelled by digital platforms’ enormous reach. This review looks at risk factors such age, gender, low self-esteem, emotional distress, loneliness, and sleep quality. Technological elements such as limitless scrolling, algorithm-driven content, and gamification exacerbate addiction. This review examines risk variables linked with social media addiction using research from Google Scholar, PubMed, ScienceDirect, and other national and international journals. The review focuses on the mental health consequences, such as anxiety, sadness, poor sleep, academic challenges, and strained relationships, which all have an influence on well-being. To combat this, the study advocates for digital literacy, ethical social media design, emotional resilience, and offline activities, as well as collaboration among researchers, educators, healthcare experts, and social media businesses to safeguard young people. This review provides a critical understanding of the intricate connections between social media addiction, mental health, and well-being, underscoring the need for collective action in a digitally connected world.